Matriarcat, maternité et pouvoir des femmes - Braun, Françoise (Anthropologie et Sociétés, 1987)
Matriarcat, maternité et pouvoir des femmes Le matriarcat remis à l'honneur au début des années 70 est un thème privilégié pour la réflexion théorique féministe en anthropologie. En tant que construction intellectuelle, le concept de matriarcat, développé par les évolutionnistes puis par les féministes, met en évidence le discours naturaliste de ces deux groupes et ses effets sur la conceptualisation des rapports de sexe. La discussion du concept de matriarcat est aussi le prétexte à une réflexion sur la maternité et le pouvoir des femmes.
Keywords: 1900-1999; 1980-1989; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques